Consumer Anxiety and Assertive Advertisement Preference: The Mediating Effect of Cognitive Fluency - Wang, Jun (Frontiers in Psychology, 2022)
Companies often seek to persuade consumers to buy products or services through assertive advertising, but such advertising is often resisted by consumers. In order to identify ways to increase consumers' preference for assertive advertising, this study starts by considering consumers’ anxiety and finds, through two between-group experiments, that the emotional state of consumers when viewing advertisements affects their attitudes towards assertive advertisements: anxious consumers have a more positive attitudes towards assertive advertisement, and processing fluency plays a mediating role in the relationship between consumer anxiety and consumer attitudes towards assertive advertisement. This study incorporates consumer anxiety into the study of assertive advertising, thus both enriching the theoretical research on assertive advertising and consumer anxiety and providing novel ideas for companies to enhance the effectiveness of their assertive advertising strategies.